(untitled) (Applied Biological Research, 2020)
Induced mutagenesis is an important tool for crop improvement and gamma (γ) ray is one of the effective physical ionizing mutagens. The present pilot study was aimed to assess the effect of γ-irradiation on mitotic cells in cluster bean (Cyamopsis tetragonoloba (L.) Taub.). The seeds of cluster bean were treated with different doses of γ rays viz., 0, 100, 200, 300, 400 and 500 Gy to analyze the effect of γ-rays on meristematic root tips. Active mitotic index and total abnormality percentage were assessed. Increasing dose of γ rays negatively influenced AMI. Higher doses severely reduced germination and seedling height, although the initial dose of 100 Gy γ-irradiation significantly enhanced them as compared to the control. The irradiated seeds showed numerous chromosomal variations such as scattering, c-metaphase, bridge formation, etc. The evidences revealed that γ-rays have mutagenic effect at mitotic level and induced decline in mitotic activity and influenced the entity of chromosomal morphology. The study also revealed that lower doses of γ irradiation can be effective in agricultural endeavours.